Reinstatement of the genus Colopalpus Pritchard and Baker (1958) and re-description of Colopalpus matthyssei Pritchard and Baker (1958), the type species of the genus (Acari, Tenuipalpidae) - Castro, Elizeu B. [UNESP]; Ochoa, Ronald; Feres, Reinaldo J. F. [UNESP]; Beard, Jennifer J.; Bauchan, Gary R. (Taylor &francis Inc, 2015)
We discuss the taxonomic history of the genus Colopalpus Pritchard and Baker 1958, and redescribe the female, male and deutonymph of the type species, C. matthyssei (Pritchard and Baker). We provide previously unknown morphological data for C. matthyssei, in addition to complementary information on the morphology of C. nambii (Castro and Feres) obtained using low temperature scanning electron microscopy (LT-SEM). Our results show that both C. matthyssei and C. nambii share characters with the genera Tenuipalpus and Brevipalpus. Based on these findings, we propose that Colopalpus be reinstated as a valid genus. We discuss the characters shared by Colopalpus, Tenuipalpus and Brevipalpus, and also provide a list of species that are transferred to the genus Colopalpus.[GRAPHICS]
Keywords: flat mites; taxonomy; Tenuipalpus; systematics; Brevipalpus; Philippines